The Impact of the Business Environment on the Effectiveness of the Implementation of the Financial Strategy of the Oil and Gas Company - Borodin, Alex; Natocheeva, Natalia; Khominich, Irina; Kulikov, Andrey; Shchegolevatykh, Natalia (International Journal of Energy Economics and Policy, 2021)
The article develops a mechanism for ensuring the growth of the efficiency of the financial strategy for the development of energy holdings based on the integration of the latter into the structure of territorial economic clusters. Based on the results of three-stage modeling, including causal analysis (Granger test), VAR vector autoregression model, and GARCH modeling, both direct and indirect influence of business environment factors at the meso-level and macro-level with a deferred effect on the financial strategy of PJSC NOVATEK was proved. The model of the mechanism of interaction between the factors of the business environment of the energy holding is structured, which allows us to establish that the key elements and conditions of the business environment that affect and determine its financial strategy can be classified depending on the groups of influence with which the holding enters into relationships, namely: consumers, competitors, suppliers, intermediaries, contact audiences. The purpose of the article is to identify the main elements of the business environment and study their impact on the company's strategy, including the formation of methods for evaluating the effectiveness of the implementation of the financial strategy, taking into account such influence. Keywords: oil and gas company, business environment, financial strategy, industrial relations, macro-environment factors. JEL Classifications: O20; Q43; Q48 DOI: https://doi.org/10.32479/ijeep.11374